Evaluation of the Effect of CD70 Co-Expression on CD8 T Cell Response in Protein-Prime MVA-Boost Vaccination in Mice - Ann-Sophie Stephan; Anna D. Kosinska; Martin Mück-Häusl; Andreas Muschaweckh; Clemens Jäger; Natalie Röder; Mathias Heikenwälder; Claudia Dembek; Ulrike Protzer (Vaccines, 2023)
Here, we investigate the potential of CD70 co-expression during viral vector boost vaccination to improve an antigen-specific T cell response. To determine the chance of activating antigen-specific T cells by CD70, we used the HBV core antigen as a model antigen in a heterologous protein-prime, Modified Vaccinia virus Ankara (MVA) boost vaccination scheme. Both the HBV core and a CD70 expression cassette were co-expressed upon delivery by an MVA vector under the same promoter linked by a P2A site. To compare immunogenicity with and without CD70 co-expression, HBV-naïve, C57BL/6 (wt) mice and HBV-transgenic mice were prime-vaccinated using recombinant HBV core antigen followed by the MVA vector boost. Co-expression of CD70 increased the number of vaccine-induced HBV core-specific CD8 T cells by >2-fold and improved their effector functions in HBV-naïve mice. In vaccinated HBV1.3tg mice, the number and functionality of HBV core-specific CD8 T cells was slightly increased upon CD70 co-expression in low-viremic, but not in high-viremic animals. CD70 co-expression did not impact liver damage as indicated by ALT levels in the serum, but increased the number of vaccine-induced, proliferative T cell clusters in the liver. Overall, this study indicates that orchestrated co-expression of CD70 and a vaccine antigen may be an interesting and safe means of enhancing antigen-specific CD8 T cell responses using vector-based vaccines, although in our study it was not sufficient to break immune tolerance.